Direct Comparison of EMLA versus Lidocaine for Pain Control in Nd: YAG 1,064 nm Laser Hair Removal - GUARDIANO, ROBERT A.; NORWOOD, Christopher W. (Dermatologic surgery, 2005)
Laser hair removal is an effective therapy for the treatment of hirsutism, hypertrichosis, and pseudofolliculitis barbae. Although side effects are uncommon, pain is described by most patients undergoing long-pulsed neodymium:yttrium-aluminum-garnet (Nd:YAG) 1,064 nm laser therapy. OBJECTIVESTo compare the efficacy of topical eutectic mixture of local anesthetics (EMLA) versus topical lidocaine (LMX) in pain control for Nd:YAG 1,064 nm laser hair removal. METHODSSixty-four patients were enrolled in a double-blind randomized study over a 6-month period. Each patient had half of the treatment area covered with EMLA and the other half with LMX 30 minutes prior to treatment. Neither was applied under occlusion. Immediately following their treatment session, patients completed a visual analog pain scale. RESULTSThere was no statistically significant difference in pain control between EMLA and LMX. However, female test subjects demonstrated lower pain scores than male test subjects. CONCLUSIONSNd:YAG 1,064 nm laser hair removal is a painful procedure. Topical anesthetics have been proven to reduce pain for laser hair removal. There is no statistically significant difference between the two most commonly used topical anesthetics for pain control in laser hair removal. Therefore, cost and minimizing potential side effects should guide the physician in selecting the appropriate anesthetic.